A highly unusual case of osmotic demyelination syndrome and extrapontine myelinolysis in a 3-month-old infant with Bartter syndrome - Giancarlo Gargano; Marco Manfredi; Simona Pedori; Francesco Di Dio; Carlotta Spagnoli; Daniele Frattini (Journal of International Medical Research, 2020)
Bartter syndrome (BS) is a rare autosomal recessive renal tubular disorder characterized by acute electrolyte imbalance, and similarly, osmotic demyelination syndrome (ODS) is a rather rare complication occurring during electrolyte imbalance. The pathological features of ODS include central pontine myelinolysis and extrapontine myelinolysis (EPM), which consist of severe damage to the myelin sheath of neurons. ODS is very rare in children. We describe a case of a 3-month-old infant with ODS and EPM associated with undiagnosed BS. ODS developed because of a sudden change in electrolyte levels and osmolality caused by acute dehydration during a gastrointestinal infection episode. Undiagnosed, untreated, and non-balanced BS was the cause of the neurological complication. Our patient represents the first case of ODS in BS, the ninth case of ODS in an infant less than one year old, and the third case of isolated EPM in such a young patient. This case report reminds us that in rare diseases, young patients tend to have genetic components.